(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India has more than 50 of its population below the age of 25 and more than 65 below theage of 35. It is found that 1 out of 5 in this age group experiences a mental, emotional or behavioraldisorder globally that is severe enough to seriously affect their daily functioning at home, school, orwithin the community. According to the World Health Organization (WHO) mental health disorders areone of the leading causes of disability worldwide. Three out of the ten leading causes of disability inpeople between the ages of 15 and 44 are mental disorders, and the other causes are often associatedwith mental disorders. Both retrospective and prospective researches have shown that most adulthoodmental disorders begin in childhood and adolescence. However, though a large proportion ofadolescents and youth are not having any diagnosed illness, they are found to be lacking incommunication and presentation skills, problem-solving capabilities and generic abilities, and an overalllow level of confidence. It has been recently reported that a significant proportion of graduates, nearly47, were found not employable in any sector, given their English language and cognitive skills. Someother problems of the youth relate with smartness, confidence, presence of mind, patience, emotions,time management and good communication skills. A recent survey highlighted the three major lackingskills in educated youth Communication skill, Analytical skill and problem-solving and Domainknowledge.